Effects of ballistic training on preseason preparation of elite volleyball players - Newton, R. U.; Kraemer, W. J.; Haekkinen, K. (Medicine & Science in Sports & Exercise, 1999)
Zielstellung: Untersuchung, ob ein ballistisches Widerstandstraining die vertikale Sprunghöhe (VJ) von schon hochtrainierten Sprungsportlern verbessert.